10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Patent ductus arteriosus (PDA) and patent foramen ovale (PFO) are two fetal cardiovascular shunts that normally undergo functional and anatomical closure shortly after birth. While PDA is a well-recognized congenital defect in veterinary cardiology, the haemodynamic interaction between PDA and PFO has received little attention, particularly in neonates. OBJECTIVES: To review the physiological and pathophysiological relationship between PDA and PFO and evaluate available evidence from veterinary and comparative human literature. REVIEW CONTENT: Increased pulmonary blood flow and secondary pulmonary hypertension associated with PDA may alter right-sided cardiac pressures and predispose affected neonates to persistent or reopened PFO, potentially resulting in interatrial shunting and cyanosis. PDA represents one of the most prevalent congenital cardiac defects encountered in canine medicine and constitutes a substantial proportion of congenital heart diseases in dogs. Conversely, PFO appears to be less frequently recognized in veterinary patients, likely because many affected animals remain clinically asymptomatic. In human medicine, persistence of the foramen ovale has been identified in approximately one-quarter of the adult population. This narrative review summarizes the physiology and pathophysiology of ductus arteriosus and foramen ovale closure, analyses the mechanisms by which PDA can influence FO patency, and discusses relevant evidence from both veterinary and human literature. CONCLUSIONS: Although no clearly documented veterinary case of concurrent PDA and PFO has been identified, comparative evidence suggests that secondary pulmonary hypertension may play an important role in this interaction. Improved understanding of this relationship may enhance diagnostic accuracy and management strategies in neonatal animals.